Applicability and Limitations of Fluorescence Intensity-Based Thermometry Using a Palette of Organelle Thermometers - Takeru Yamazaki; Xiao Liu; Young-Tae Chang; Satoshi Arai (Chemosensors, 2023)
Fluorescence thermometry is a microscopy technique in which a fluorescent temperature sensor records temperature changes as alterations of fluorescence signals. Fluorescence lifetime imaging (FLIM) is a promising method for quantitative analysis of intracellular temperature. Recently, we developed small-molecule thermometers, termed Organelle Thermo Greens, that target various organelles and achieved quantitative temperature mapping using FLIM. Despite its highly quantitative nature, FLIM-based thermometry cannot be used widely due to expensive instrumentation. Here, we investigated the applicability and limitations of fluorescence intensity (FI)-based analysis, which is more commonly used than FLIM-based thermometry. Temperature gradients generated by artificial heat sources and physiological heat produced by brown adipocytes were visualized using FI- and FLIM-based thermometry. By comparing the two thermometry techniques, we examined how the shapes of organelles and cells affect the accuracy of the temperature measurements. Based on the results, we concluded that FI-based thermometry could be used for “qualitative”, rather than quantitative, thermometry under the limited condition that the shape change and the dye leakage from the target organelle were not critical.